2002
DOI: 10.1002/humu.9103
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphate dehydrogenase (G6PD) variants in Malaysian Malays

Abstract: We performed DNA analysis using cord blood samples on 86 male Malay neonates diagnosed as G6PD deficiency in the National University of Malaysia Hospital by a combination of rapid PCR-based techniques, single-stranded conformation polymorphism analysis (SSCP) and DNA sequencing. We found 37.2% were 871G>A (G6PD Viangchan), 26.7% were nt 563 C>T (G6PD Mediterranean) and 15.1% were 487G>A (G6PD Mahidol) followed by 4.7% 1376G>T (G6PD Canton), 3.5% 383T>C (G6PD Vanua Lava), 3.5% 592C>T (G6PD Coimbra), 2.3% 1388G>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 23 publications
7
80
2
Order By: Relevance
“…In that study, 21 cases of G6PD Viangchan (67.7%) were found among 31 cases of G6PD deficiency, while G6PD Mahidol comprised only 9.7% (3/31). Ainoon et al (2003) demonstrated nine G6PD variants among 84 cases of G6PD deficiency in Malaysian Malays. The main variants were G6PD Viangchan (38.1%), G6PD Mediterranean (27.4%), and G6PD Mahidol (15.5%).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In that study, 21 cases of G6PD Viangchan (67.7%) were found among 31 cases of G6PD deficiency, while G6PD Mahidol comprised only 9.7% (3/31). Ainoon et al (2003) demonstrated nine G6PD variants among 84 cases of G6PD deficiency in Malaysian Malays. The main variants were G6PD Viangchan (38.1%), G6PD Mediterranean (27.4%), and G6PD Mahidol (15.5%).…”
Section: Resultsmentioning
confidence: 97%
“…This variant is common in Laos (100%) (Iwai et al 2001), Thailand (67.7%) (Nuchprayoon et al 2002), and Malaysia (38.1%) (Ainoon et al 2003). We did not detect G6PD Mediterranean, a common variant in Mediterranean countries, Middle Eastern countries, Pakistan and India (Luzzatto and Notaro 2001), and Nepal (Matsuoka et al 2003a).…”
Section: Resultsmentioning
confidence: 99%
“…Many published pharmacogenetic studies (Meyer 1994;Ainoon et al 1999;Hustert et al 2001;Iwai et al 2001;Xie et al 2001;Ainoon et al 2001;Chang et al 2002;Chowbay et al 2003;Tang et al 2002;Kroetz et al 2003;Tan et al 2003) focused on individual genes and limited mutations. There is restricted information on allele frequency and LD distributions of these genes on a genome-wide scale.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, this mutation was also reported from South East Asia, mainly Malaysia and Indonesia (Ainoon et al 2003;Kawamato et al 2006). However, this mutation has not been reported from India.…”
Section: Discussionmentioning
confidence: 96%